DESCARTES VE SPİNOZA DÜŞÜNCESİNDE GERÇEK İYİ KAVRAMI - Nurten Gökalp (Felsefe Dünyası)
The struggle of the searching the actual good is important in the philosophy especially 17. century. In this essay, it will be examined this problem related with Descartes’ and Spinoza’s thoughts. According to Descartes, the highest good which is the final aim of ethics is related with the visdom. To him, in the light of reason we can build a structure of knowledge. Pure reason can find its clear and distint ideas and what exists beyond those ideas. Man who has gain the clear and distint ideas control his life and his passions. Actual good is to have those ideas and using them to control his life. For Spinoza actual good is necessarily related with God. Because all truhts follow necesarily from the nature of God as a thinking being but approached from the stanpoint of God as an extended beingit is equally true one state of universe as a arrangement of bodies follows from another by necessary laws. ‘The order and connection of ideas is the same as the order and connection of things.’ All good and evil is relative to our human standars. Things come to be good because we desire them. Spinoza define an adequate idea as one which in so far as it is considered in itself without reference to the object, has all properties or internal signs of a true idea. God as a system of modes it is enough to inspire that intellectual love of God. To be able to identify himself not only preferable to any wordly good; it is preferable to the traditional immortality conceived as the endless existence of the human person, enjoying the favor of God.